The Eurozone Crisis and the Future of Europe The Political Economy of Further Integration and Governance - Kumar, Rajeesh. (International Political Economy Series,, 2014)
The authors uncover the roots of the eurozone crisis, focusing on how this can be solved against the backdrop of a very deep financial and economic crisis and its strong social impact. Looking at the impact of the financial crisis on the eurozone, they explore the European Union's recent and future developments.